From the Push of Fear, to the Pull of Hope: Learning by design - Stephen Sterling (Environmental Association of Southern Africa, 2007)
One of the benefits of getting older is gaining an overview of things. Over time, you obtain a clearer standpoint from which to view trends, patterns and changes. All too quickly, you also find yourself changing, from a young advocate, passionate about environmental education and keen to learn, to one of the old guard, still committed but possibly a bit wiser about the possibilities of and barriers to change. In my study at home, and immediately visible from my desk, are shelves full of reports, books, manuals which I've collected over a 30-year period. I ought to throw away - sorry, recycle - more than I do, but I've always been a bit of an archivist. It's fascinating to look back at what we were saying 10, 20, 30 and more years ago. And I wonder how much has really changed, and how deeply we are imbued with and seduced by the Western idea of intellectual progress, so that 'old ideas' must by their nature, be less relevant, less insightful than 'new ideas'.